The disability profile in primary care may depend on the type of care and pain aspects - Fernanda de Assis da Costa Ferreira; Angela Baroni de Góes; Raquel Aparecida Casarotto; Tiótrefis Gomes Fernandes; Shamyr Sulyvan de Castro; Ana Carolina Basso Schmitt (Revista de Saúde Pública)
ABSTRACT OBJECTIVE: To investigate the relationship between sociodemographic factors, musculoskeletal pain and its characteristics, and the type of primary health care received with self-reported disability. METHODS: This is a cross-sectional study, interviewing individuals selected from spontaneous demand for health care in two types of care: health center and family health unit. Disability was investigated using the World Health Organization Disability Assessment Schedule (WHODAS) 2.0 and characteristics of intensity, frequency, duration, number of pain sites, and regions. Measures of association between predictors and disability were performed with non-parametric statistical tests, whereas non-parametric regression models were presented for pain characteristics and for the general population. RESULTS: In total, 2.3% of family health users and 7.2% of health center users had severe levels of disability. Health center users had more self-reported disability than family health users (p < 0.001). Fewer years of life (p = 0.034) and lower per capita income quintile (p = 0.014) were associated with greater disability. The most intense pain and pain in the greatest number of sites increased the disability score by 1.8 (95%CI = 1.0–2.6) and 6.3 (95%CI = 0.1–12.2) points, respectively. CONCLUSION: Users who had more disabilities sought care at walk-in health centers, had lower per capita income, presented musculoskeletal pain of worse intensity, and pain in a greater number of sites.